MILLET FLOUR SUBSTITUTION FOR EGG ROLLS SEMPRONG - Dewi Eka Murniati, MM, Jawani Prawita Sari (Prosiding Pendidikan Teknik Boga Busana, 2020)
Semprong is a traditional cookies from Indonesia. Semprong is tube or roll shaped and tastes uniquely. It also could be trianglular and square shaped. Semprong is made from the main ingredients of wheat flour and rice flour. This research is aimed to: (1) Invent the right recipe of semprong that substituted by foxtail millet flour, (2) Know locals acceptance of semprong and also encourage them developing other patisserie products which made of foxtail millet flour so that produced high quality products. Research type used is research and development based on 4D model (Define, Design, Develop, Disseminate). Define is the product planning stage by selecting one recipe out of three reference recipes. Design is the stage of making a product development plan from the selected reference recipe. Develop is the stage of validation test by selected expert. Disseminate is the stage of products testing to panelists and products introduction to locals. This research was taken place at the Catering Laboratory, Department of Food and Clothing Engineering, Faculty of Engineering, Universitas Negeri Yogyakarta between January-April 2019. Each product was taken for samples while the testing instruments are experimental forms, validation forms, panelist sensory test forms, and exhibition preference test forms. Data analysis used is both qualitatively and quantitatively description method. Research results: (1) The proper recipe for semprong with millet flour substitution was turned out by 55%. Other ingredients are cornstarch, eggs, margarine, sugar, thick coconut milk, vanilla powder, black sesame seed. Sponge method was used and the dough was manually molded. (2) Local’s level of acceptance is showed by the score of many aspects; 3,67 by color aspect, 3,68 by flavor aspect, 3,82 by texture aspect, 3,88 by taste aspect and 3,9 by the whole product aspect. Assessment score was ranged 1 – 4 which means 1 for very dislikeable and 4 for very likeable score. Mean score of the products is above 3, so it can be concluded that semprong with foxtail millet is well accepted among locals. Keywords: Semprong (cookies), Foxtail Millet